Roundtable viewpoints : - Robertson, Christopher J. (McGraw-Hill, 2007)
ROUNDTABLE VIEWPOINTS: INTERNATIONAL BUSINESS offers varying perspectives on important issues and provides readers with balanced and fair coverage of a topic to form their own opinion or to support their research. This reader is designed to address a number of different issues regarding international business. Each issue question is relevant to the topic and guides readers through the readings. The controversy and different views among the captivating readings is readily apparent to the reader and stimulates discussion. The 3-5 selections per issue are current, culled from a variety of sources, and relate to the most popular issues surrounding the topic.